'Just another border incident': The Rann of Kutch and the 1965 India–Pakistan War. Issue 5 (29th July 2019) - Chaudhuri, Rudra
ABSTRACT: The India–Pakistan War of September 1965 has attracted little attention in the larger body of work on South Asia. Further, almost nothing has been written on the earlier skirmish, in April 1965, between Indian and Pakistani security forces in the Rann-of-Kutch, an uninhabited salt marsh. This article argues that the limited conflict in the Rann, its immediate consequences, and its impact on Pakistani military and civilian leaders were central to Pakistan's consideration of a military solution to the ongoing dispute in Kashmir, which then led to Indian retaliation and the outbreak of war.